1994
DOI: 10.1161/01.hyp.24.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl sulfate lowers plasma insulin and blood pressure in spontaneously hypertensive rats.

Abstract: Spontaneously hypertensive rats (SHR) are hyperinsulinemic compared with their Wistar-Kyoto (WKY) controls. Since previous studies have demonstrated that vanadyl sulfate lowers insulin levels in nondiabetic rats, we used vanadyl to explore the relation between hyperinsulinemia and hypertension. In a prevention study, 5-week-old SHR and WKY rats were started on long-term vanadyl sulfate treatment. Vanadyl in doses of 0.4 to 0.6 mmol/kg per day lowered plasma insulin (252±22.8 versus 336±12.6 pmol/L, treated ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 42 publications
2
19
0
3
Order By: Relevance
“…In addition, we recently introduced a novel vanadyl (IV) compound having V O 2ϩ chelate, bis(1-oxy-2-pyridinethiolato) oxovanadium (IV), [VO[(OPT)], as potent activator of protein kinase B/Akt, thereby protecting cardiomyocytes from ischemia/ reperfusion injury in rats 18 and in mouse brain ischemia. 21 Consistent with our findings, the vanadyl (IV) form of vanadium possesses cardioprotective action 22 and antihypertensive action in spontaneous hypertensive rats and in fructose-induced hypertensive rats [23][24][25] through unknown mechanisms.…”
supporting
confidence: 84%
“…In addition, we recently introduced a novel vanadyl (IV) compound having V O 2ϩ chelate, bis(1-oxy-2-pyridinethiolato) oxovanadium (IV), [VO[(OPT)], as potent activator of protein kinase B/Akt, thereby protecting cardiomyocytes from ischemia/ reperfusion injury in rats 18 and in mouse brain ischemia. 21 Consistent with our findings, the vanadyl (IV) form of vanadium possesses cardioprotective action 22 and antihypertensive action in spontaneous hypertensive rats and in fructose-induced hypertensive rats [23][24][25] through unknown mechanisms.…”
supporting
confidence: 84%
“…Until now, four vanadium compounds, namely, sodium orthovanadate (OV) (42,43); vanadyl sulfate (VS) (20,22,30); bis(maltolato)oxovanadium (IV) [BMOV] (21,44,45); and VO(OPT) (18,19,28), have been found to have cardioprotective effects in different heart injury models (Fig. 1).…”
Section: Akt Activator Vanadium Compounds For Treatment Of Cardiac DImentioning
confidence: 99%
“…Among these, the cardioprotective effects of vanadium has been studied in great detail, and several studies have demonstrated that the vanadyl (IV) form of vanadium possesses cardioprotective properties (15) in diabetic rats (16,17), myocardial ischemia /reperfusion-induced injury in rats (18,19), spontaneously hypertensive rats (SHR) (20,21), and fructose-fed rats (22), representing a genetic and dietinduced model of hypertension (23). Among the several oxidation states of vanadium II to V, vanadium ion in living cells exists exclusively as vanadyl (IV) cation and a small amount of vanadate (V) anion (24).…”
Section: Introductionmentioning
confidence: 99%
“…24 However, vanadate (in 40 to 80 mol/L range) may also promote endothelium-dependent vasodilation, 30 may reduce systolic blood pressure in spontaneously hypertensive rats 31 and may also ameliorate the exaggerated vasoconstriction in aortic tissue from the hyperinsulinemic/ insulin-resistant obese Zucker rat. 32 McNeill and coworkers 31,33,34 have shown that long-term vanadium treatment of insulin-resistant/diabetic rats led to reduction in BP, perhaps related to normalization of metabolic alterations in the insulin-resistant and diabetic state by vanadium compounds. The changes in erythrocyte Mg i levels may be intimately linked to changes in erythrocyte Ca i levels.…”
Section: Discussionmentioning
confidence: 99%